2016
DOI: 10.1155/2016/4173185
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Putamen and Insula Activation by Both Left and Right GB34 Acupuncture Stimulation: An fMRI Study on Healthy Participants

Abstract: The modulatory effects on the brain during right versus left side acupuncture stimulation of the same acupuncture point have been a subject of controversy. For clarification of this important methodological issue, the present study was designed to compare the blood oxygen level-dependent responses of acupuncture stimulation on the right versus left Yanglingquan (GB34). Twenty-two healthy subjects received right or left GB34 acupuncture. Our results show that acupuncture on the left GB34 induced neural response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…These structures play a very important role in the involvement of the ganglia in motor acts. [ 16 ] It is also part of a circuit that is affected by numerous neurological alterations such as in Parkinson disease. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures play a very important role in the involvement of the ganglia in motor acts. [ 16 ] It is also part of a circuit that is affected by numerous neurological alterations such as in Parkinson disease. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Finally, another study performed acupuncture stimulation and found an activation of the ipsilateral putamen to the stimulated zone. [ 16 ] In contrast, other investigators compared the motor task with tactile stimulation and reported lower ipsilateral hemisphere activity during the execution of a motor task. [ 26 ] Future studies should improve current knowledge to better understand the functional specialization of the cerebral hemispheres and the recording of tactile, proprioceptive, and motor action information which could help the tactile stimulation treatments develop on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicated that acupuncture stimulation could decrease abnormally elevated glucose metabolism in the postcentral gyrus ( Liu et al, 2012 ), and needling at ST36 could normalize the fMRI signals in the postcentral gyrus ( Li et al, 2014 ). However, acupuncture does not always elicit brain responses in the postcentral gyrus, although brain responses have been observed in various acupuncture-related neuroimaging studies ( Yan et al, 2005 ; Yang et al, 2014 ; Yeo et al, 2016 ; Zheng et al, 2018 ). This study indicated significant increases of ALFF values in the postcentral gyrus in all FD patients after acupuncture was performed, with increased ALFF values positively correlating with improvements in SID scores.…”
Section: Discussionmentioning
confidence: 99%
“…GB34 acupuncture can activate the above damaged regions and putamen in patients with PD and activate the cortical neural networks in these brain regions. Another fMRI study by Yeo et al [18] showed that reduction in neural responses in the brains of patients with PD were more widespread, including the putamen, thalamus, and supplementary motor areas, as compared with those in healthy subjects. GB34 acupuncture can activate the above damaged regions and increase neuronal activity in the regions related to PD, including the substantia nigra, caudate nucleus, thalamus, and putamen.…”
Section: Visual Neuroimaging Research Of Acupuncture In Parkinson’s Diseasementioning
confidence: 99%